Synergistic effects of epigallocatechin gallate and l-theanine in nerve repair and regeneration by anti-amyloid damage, promoting metabolism, and nourishing nerve cells - Xie, Xinya; Wan, Juan; Zheng, Xin; Pan, Wenjing; Yuan, Jiayi; Hu, Baozhu; Feng, Meiyan; Liu, Zhonghua; Cai, Shuxian (Frontiers in Nutrition, 2022)
Green tea has significant protective activity on nerve cells, but the mechanism of action is unclear. Epigallocatechin gallate (EGCG) and N-ethyl-L-glutamine (L-theanine) are the representative functional components of green tea (Camellia sinensis). In this study, an AD model of Aβ25-35-induced differentiated neural cell line PC12 cells was established to study the synergistic effect of EGCG and L-theanine in protecting neural cells. The results showed that under Aβ25-35 stress conditions, mitochondria and axons degenerated, and the expression of cyclins was up-regulated, showing the gene and protein characteristics of cellular hyperfunction. EGCG+L-theanine inhibited inflammation and aggregate formation pathways, significantly increased the percentage of G0/G1 in the cell cycle, downregulated the expression of proteins such as p-mTOR, Cyclin D1 and Cyclin B1, upregulated the expression of GAP43, Klotho, p-AMPK and other proteins, promoted mitochondrial activity and energy metabolism, and had repair and regeneration effects on differentiated nerve cells. The synergistic mechanism study showed that under the premise that EGCG inhibits amyloid stress and inflammation and promotes metabolism, L-theanine could play a nourish nerve effect. EGCG+L-theanine keeps differentiated nerve cells in a quiescent state, which is beneficial to the repair and regeneration of nerve cells. In addition, EGCG+L-theanine maintains the high-fidelity structure of cellular proteins. This study revealed for the first time that the synergistic effect of EGCG with L-theanine may be an effective way to promote nerve cell repair and regeneration and slow down the progression of AD. Our findings provide a new scientific basis for the relationship between tea drinking and brain protection.